PENGARUH FAKTOR PRODUKSI TERHADAP PENDAPATAN DAN IMPLIKASINYA TERHADAP NILAI TUKAR PETANI KENTANG (Studi Kasus Petani Kentang di Kecamatan Kejajar – Wonosobo, Kecamatan Ci- kajang – Garut dan Kecamatan Pangalengan - Bandung Barat) - Noor Salim, Darwati Susilastuti, dan Rini Setyowati (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2019)
Potatoes can essentially be alternative food substitutes for staple food (rice) in Indonesia because potatoes have a high content of carbohydrates and are an important commodity. The productivity of potato farmers in Indonesia is still low, while the potential for production and demand is quite high. Production fac-tors in potato farming have not been optimally sought, it is necessary to know the factors of production that predominantly influence farmers' resources such as education level, farming skills, institutional farming, still low. The purpose of this study is to determine the income (Return Cost Ratio), to know the simultaneous and partial effects of production factors in the form of land, seeds, fertilizers, pesticides, labor and long farming to the income of potato farming. The proposed hypothesis is: potato farming at research sites is advanta-geous and feasible to cultivate; there are significant and positive influence of fac-tors of production, land area, seeds, fertilizer, pesticide, labor, and length of farming simultaneously and partially to the income of potato farming Determina-tion of research area and respondent is done by purposive that is potato farmer in region of potato producing center mostly in Pangalengan District - South Ban-dung. The results showed that the average farming cost incurred by potato far-mers in the Pangalengan District - South Bandung is Rp. 58.166.733, - and its receipt of Rp. 93.690.000, - per planting season. So the potato farming done by farmers in Pangalengan has been efficient with R / C ratio obtained by 1, 61. The estimation results show that simultaneously variable of land area, seeds, fertilizer, Pesticide, labor, and length of farming have the significant effect on farm income potato with Coefficient of Determination of 0.672. Partially variable of land have the real and positive effect on farmer income. The cost of seeds and labor nega-tively affect farmers' income. Land area is the dominant factor in potato farming. The proposed suggestion is that the land available for potato cultivation should be further expanded so that the potato production of farmers can be increased due to the effect of land area on real and positive income. Keywords: Production Factor, Potato Exchange Rate